Enhancing Web Accessibility for Specially Abled Users: An Evaluation of Top-Ranked Open Universities in India according to WCAG Standards - Das, Subham; Bhattacharya, Udayan (Journal of Information and Knowledge, 2025)
Purpose: This study examines the digital accessibility of websites from top-ranked open universities in India, evaluating their compliance with the Web Content Accessibility Guidelines (WCAG). The focus is on understanding how these institutions adhere to WCAG principles and identifying the accessibility challenges faced by specially abled users. The study examines universities ranked by the latest National Institutional Ranking Framework (NIRF), emphasising the importance of Open and Distance Learning (ODL) and online modes, which are vital for students with physical disabilities. Access to digital resources is crucial for these users, and the university website is often the first point of access. Methodology: The study involves a comprehensive review of WCAG principles and a structured survey of top-ranked Indian open university websites. These websites were evaluated for compliance with WCAG standards. The analysis focused on identifying patterns and gaps in digital accessibility. Findings: The evaluation of three prominent open universities in India reveals varying levels of adherence to WCAG standards. IGNOU demonstrates a balanced performance. NSOU, on the other hand, faces significant challenges. BAOU presents a moderate level of compliance. The study underscores the need for continuous efforts to ensure that higher education websites are fully inclusive and accessible to all students, regardless of their abilities. Value: This study offers a detailed analysis of digital highlighting, including both strengths and areas for improvement. It underscores the importance of accessible digital experiences for specially abled users in higher education, particularly in accessing resources through ODL and online education.